Pressure overload and volume overload-induced chronic heart failure are associated with characteristic left ventricular myocardial proteomic alterations. (3rd October 2022) - Ruppert, M; Barta, B A; Sayour, A A; Olah, A; Nagy, D; Balint, T; Benke, K; Schilling, O; Merkely, B; Radovits, T
Abstract: Introduction: Hemodynamic overload induces pathological remodeling of the left ventricle (LV) and eventually heart failure (HF). The two types of chronic hemodynamic stress, namely pressure overload (PO) and volume overload (VO) evoke characteristically different functional and structural alterations in the myocardium. Nevertheless, whether PO- and VO-induced HF are also associated with distinct LV proteomic alterations has not been investigated yet. Aim: Hence, we thought to perform a proteomic analysis on LV myocardial samples from rat models of PO- and VO-induced HF. Methods: PO–induced HF was evoked by transverse aortic constriction (TAC). VO–induced HF was established by creating an aortocaval fistula (ACF). Age-matched sham-operated animals served as controls for TAC (ShamT) and ACF (ShamA), respectively. Pressure-volume (P-V) analysis, echocardiography, histology and quantitative real-time PCR were carried out to provide a detailed characterization of the two HF models. Peptides obtained via the digestion of myocardial proteins with trypsin and LysC were labeled with isobaric tags (TMT16) and measured with LC-MS/MS in a bottom-up explorative proteomic approach. Differential expression and gene ontology enrichment analysis (GO:BP) was carried out on summarized protein reporter ion intensities. Results: In both the TAC and ACF groups, presence of typical signs and symptoms of HF (dyspnea at rest, fatigue, ascites) increased lung-to-tibial length ratio and elevated LV natriuretic peptide mRNA expression levels confirmed the development of advanced HF. Furthermore, the TAC model was associated with massive wall thickening, concentric LV hypertrophy (LVH), marked interstitial fibrosis and substantially impaired active relaxation and passive filling (slope of end-diastolic P-V relationship: 0.103±0.015 vs. 0.023±0.003mmHg/μl, TAC vs. ShamT, P<0.001). In contrast, the ACF model was predominantly characterized by LV dilatation, eccentric LVH, moderate fibrosis and severely reduced LV contractility (slope of end-systolic P-V relationship: 0.5±0.1 vs. 2.3±0.3mmHg/μl, ACF vs. ShamA, P<0.001). Proteomic analysis revealed that out of the 4691 identified and quantified proteins, 1404 and 913 have shown upregulation, while 1359 and 886 downregulation in the TAC and ACF groups respectively compared to their corresponding sham groups. GO:BP analysis has indicated that the downregulation of mitochondrion organization, ATP metabolic processes and oxidative phosphorylation and the upregulation of actin cytoskeleton organization were the most profound alterations in the TAC model. In contrast, the ACF model was associated with robust downregulation of fatty acid oxidation and upregulation of endocytosis, defense and immune response on the proteomic level. Conclusions: PO and VO-induced advanced HF are not only associated with characteristically different functional and structural remodeling but also with distinct LV proteomic alterations. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Office (NKFIH) of Hungary